Advanced Mechanochemistry Device for Sustainable Synthetic Processes - Gomes, Carla (2020)
Mechanochemistry is an alternative for sustainable solvent-free processes that has taken the big step to become, in the near future, a useful synthetic method for academia and the fine chemical industry. The apparatus available, based on ball milling systems possessing several optimizable variables, requires too many control and optimization experiments to ensure reproducibility, which has limited its widespread utilization so far. Herein, we describe the development of an automatic mechanochemical single-screw device consisting of an electrical motor, a drill, and a drill chamber. The applicability and versatility of the new device are demonstrated by the implementation of di- and multicomponent chemical reactions with high reproducibility, using mechanical action exclusively. As examples, chalcones, dihydropyrimidinones, dihydropyrimidinethiones, pyrazoline, and porphyrins, were synthesized with high yields. The unprecedented sustainability is demonstrated by comparison of EcoScale and E-factor values of these processes with those previously described in the literature.